Productive and Ecological Aspects of Mixed Cropping System - Wenda-Piesik, Anna; Synowiec, Agnieszka (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Mixed cropping, also known as inter-cropping or co-cultivation, is a plant production system that involves planting two or more species (or cultivars) in the same field in a variable order-row or rowless-simultaneously. Mixed cropping plays an important role in sustainable agriculture by adding value to crop rotations and agroecosystems. Scientific investigations on environmentally friendly mixed cropping should be supported by studies on the direct costs and long-term benefits that are the most relevant to farmers. Meeting the need to strengthen the scientific basis for mixed crops, the papers in this Special Issue enhance our understanding of the following: The selection of species and cultivars for a mixed crop system as well as the choice of agricultural treatments that will secure a stable yield of mixtures; Inter- and intra- species competition of plants in a canopy; Ecological intensification approaches and opportunities for maximizing crop performance and yield in mixtures; The effects of mixed crops on crop rotations; The short- and long-term ecosystem benefits of mixtures; The effects on pests and the biodiversity of agroecosystems provided by mixtures; The economic aspects of adopting the mixtures in farms; The nutritive value of mixtures for livestock; Other topics related to the mixed cropping.